2001
DOI: 10.2527/2001.793582x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding high-oil corn to beef steers on carcass characteristics and meat quality.

Abstract: To assess the effects of feeding high-oil corn on carcass characteristics and meat quality, 60 yearling steers were fed high concentrate diets containing either control corn (82% of diet), high-oil corn (82% of diet), or high-oil corn at a concentration that was isocaloric with the control diet (74% of diet). After being fed for 84 d, steers were slaughtered. At 72 h postmortem, carcass data were collected and rib sections from five steers grading U.S. Choice and five steers grading U.S. Select from each treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
6
16

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 29 publications
8
53
6
16
Order By: Relevance
“…Higher values were obtained by Andrae et al (2001), who evaluated diets containing maize with high oil levels in confi ned young bulls, with an average obtained value of 56.20 mg/100 g. Padre et al (2007) found a total cholesterol level of 43.22 mg/100 g in the Longissimus muscle. However, similar results to this experiment were obtained by Padre et al (2006), who analysed a sample of striploin and found a value of 52.00 mg/100 g of muscle.…”
Section: Discussionmentioning
confidence: 96%
“…Higher values were obtained by Andrae et al (2001), who evaluated diets containing maize with high oil levels in confi ned young bulls, with an average obtained value of 56.20 mg/100 g. Padre et al (2007) found a total cholesterol level of 43.22 mg/100 g in the Longissimus muscle. However, similar results to this experiment were obtained by Padre et al (2006), who analysed a sample of striploin and found a value of 52.00 mg/100 g of muscle.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier work with beef cattle has found that feeding diets containing whole oilseeds increased back fat (Felton and Kerley, 2004), though others found that diets high in oil did not affect fat thickness (Andrae et al, 2001). …”
Section: Table 10mentioning
confidence: 99%
“…Sólo el glicerol puede ser utilizado en la gluconeogénesis (Gurr et al, 2002;Pethick et al, 2004;Hess et al, 2008). Cuando las dietas incluyen fuentes lipídicas como suTabla I. Efecto de la dietas sobre la concentración del glucógeno muscular (Diet effect on muscle glycogen concentration plemento concentrado en energía, se ha observado que los animales en crecimiento tienden a incrementar los depósitos de grasa corporal a partir de los ácidos grasos provenientes directamente de la dieta (Andrae et al, 2001). Asimismo, un incremento de ácidos grasos en plasma podría disminuir el catabolismo de la glucosa a través de la secreción de insulina, generando una mayor capacidad de almacenamiento de glucosa en el tejido muscular y hepático (Chilliard, 1993).…”
Section: Generalidadesunclassified